29. Integrated Learning Management Systems - Clark, Sharon; Cossarin, Mary; Doxsee, Harry; Schwartz, Linda (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2004)
Four integrated learning management packages were reviewed: CentraOne, IntraLearn, Lyceum, and Silicon Chalk. These products provide different combinations of synchronous and asynchronous tools. The current report examines the products in relation to their specific value for distance educators and students.